Factors Affecting Disseminated Intravascular Coagulation (DIC) in Post Partum Women: A Meta Analysis - Musyawamah Musyawamah; Lili Farlikhatun (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Disseminated intravascular coagulation (DIC) is one of the risk factors that can increase mortality with a prevalence of about 82% when bleeding occurs. Information on how influential maternal characteristics are to the incidence of DIC in postpartum mothers will be very useful in detecting and performing care, however. Indonesian researchers are still lacking in conducting studies on the impact and influence of maternal characteristics with the incidence of DIC on postpartum mothers. The purpose of this meta-analysis was to find out what factors influence the incidence of DIC in postpartum mothers. Primary data is obtained by searching several indexing including: PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. By using the search keywords "factor associated AND DIC", "characteristic AND DIC", " post partum AND DIC AND adjusted odds ratio", and "factors AND DIC AND adjusted odds ratio" . Inclusion criteria, including: Full paper article with observational study design from 2018-2023. Covid-19 infection and DIC gave Odds Ratio results (OR 2.32; 95% CI: 1.67 – 3.22; p value < 0.001). Hypertension and DIC Odds Ratio (OR 2.17; 95% CI: 0.84 – 5.58; p value < 0.11). and eclampsia and DIC give an Odds Ratio result (OR 24.64; 95% CI: 6.50– 93.39; p value < 0.001).